2018
DOI: 10.1177/0300891618765555
|View full text |Cite
|
Sign up to set email alerts
|

MEF2C promotes gefitinib resistance in hepatic cancer cells through regulating MIG6 transcription

Abstract: Our study provides novel insight into the regulation mechanism of MIG6 and suggests potential implications for the therapeutic strategies of gefitinib resistance through inhibiting MEF2C in hepatic cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…MIG-6 (or ERRFI1) is a negative regulator of all members of the ErbB receptor family, and involvement of the EGFR signaling pathway has been investigated (Endo et al, 2017). Research indicates that ERRFI1 plays an important role in the response of cancer cells to chemotherapeutic agents (Li et al, 2014;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MIG-6 (or ERRFI1) is a negative regulator of all members of the ErbB receptor family, and involvement of the EGFR signaling pathway has been investigated (Endo et al, 2017). Research indicates that ERRFI1 plays an important role in the response of cancer cells to chemotherapeutic agents (Li et al, 2014;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Agatheeswaran et al found that MEF2C is overexpressed in myeloid leukemia 28 . Zhang et al observed an increased MEF2C in liver cancer, whereas its knockdown inhibits cell growth and protects cancer cells against chemoresistance 29 . Ni et al demonstrated that silencing of MEF2C not only represses endometrial carcinoma metastasis and proliferation of cells in vitro but also hampers tumor xenograft growth in vivo 30 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 Zhang et al observed an increased MEF2C in liver cancer, whereas its knockdown inhibits cell growth and protects cancer cells against chemoresistance. 29 Ni et al demonstrated that silencing of MEF2C not only represses endometrial carcinoma metastasis and proliferation of cells in vitro but also hampers tumor xenograft growth in vivo. 30 Herein, we also observed that MEF2C was overexpressed in OS cells and tumors, suggesting that MEF2C may also be an underlying onco‐protein in OS progression.…”
Section: Discussionmentioning
confidence: 99%
“…MEF2C-mediated VEGF-induced vasculogenic mimicry, angiogenesis, and invasion, as well as inhibition of β-catenin-induced tumor growth ( Bai et al, 2015 ). Besides, MEF2C was upregulated in gefitinib-resistant cancer tissues and associated with gefitinib resistance in hepatic cancer cells ( Zhang et al, 2018 ). He et al (2021) found that EOMES was down expressed in tissue samples and related to the advanced stage and poor prognosis of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%